Association between ambient temperature and stroke risk in high-risk populations: a systematic review - Danh, Nathan; Ho, Chau; Ford, Emily; Zhang, Jian; Hong, Hua; Reid, Christopher; Xu, Dan (Frontiers in Neurology, 2024)
Background: Significant associations exist between ambient temperature and stroke risk, but results in high cardiovascular risk populations are lacking. This systemic review summarized current evidence on ambient temperature and overall stroke risk in high cardiovascular risk population.Methods: We performed a systematic literature search across MEDLINE, Embase, PsycINFO, CINAHL, Web of Science, and GEOBASE, from inception to 3 July 2023 to identify all population-based studies. Eligible studies screened by independent reviewers recruited individuals aged 18 years and over, where at least 80% of participants who had a high cerebral vascular diseases (CVD) risk profile. The primary outcomes are stroke morbidity and mortality, while secondary outcomes are morbidity and mortality of ischaemic stroke (IS), intracranial cerebral haemorrhage (ICH), subarachnoid haemorrhage (SH).Results: The database searches identified 9025 articles. After removing duplicates, 7647 articles were screened in title and abstract to identify 380 articles for full-text screening. After full-text screening of 380 articles by two independent reviewers, 23 articles were included in the review.Conclusions: The evidence for an association between ambient temperature and stroke incidence is that lower temperature was more likely to increase morbidity and mortality risk of both haemorrhagic and ischaemic stroke in the elderly. Conversely, higher ambient temperature is significantly associated with intracranial haemorrhage risk, but decreased risk with IS. Higher and lower ambient temperature consistently increase stroke risks in patients with comorbidities of congestive heart failure and dyslipidaemia. This evidence implies the need to establish clinical guideline for preventive intervention in patients with high stroke risks during extreme ambient temperature.